2000
DOI: 10.1074/jbc.m000322200
|View full text |Cite
|
Sign up to set email alerts
|

The Osteoblast-specific Transcription Factor Cbfa1 Contributes to the Expression of Osteoprotegerin, a Potent Inhibitor of Osteoclast Differentiation and Function

Abstract: Bone formation and resorption are tightly coupled under normal conditions, and the interaction of osteoclast precursors with cells of the osteoblast lineage is a prerequisite for osteoclast formation. Cbfa1 is an osteoblast-specific transcription factor that is essential for osteoblast differentiation and bone formation. At present, it is not known whether Cbfa1 regulates any of the osteoblast-derived factors involved in the bone resorption pathway. Osteoprotegerin (OPG) is an osteoblastsecreted glycoprotein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 46 publications
7
122
0
2
Order By: Relevance
“…Therefore, we believe that during root resorption, Runx2 was able to bind with the same site to increase the expression of RANKL in PDLSCs. Additionally, previous study demonstrated that 12 putative Cbfa1/Runx2-binding elements (osteoblast-specific element 2-OSE 2 ) were presented in human OPG promoter sequence and Runx2 could bind to the proximal OSE 2 to increase OPG expression level [36]. Further, when doxycycline was used to induce increased expression of Runx2 in ST2 cells (a bone marrow-derived mesenchymal pluripotent cell line), the differentiation of cocultured splenocytes into osteoclasts was enhanced along with the inhibition of OPG [37], which result was consistent with our data.…”
Section: Figmentioning
confidence: 99%
“…Therefore, we believe that during root resorption, Runx2 was able to bind with the same site to increase the expression of RANKL in PDLSCs. Additionally, previous study demonstrated that 12 putative Cbfa1/Runx2-binding elements (osteoblast-specific element 2-OSE 2 ) were presented in human OPG promoter sequence and Runx2 could bind to the proximal OSE 2 to increase OPG expression level [36]. Further, when doxycycline was used to induce increased expression of Runx2 in ST2 cells (a bone marrow-derived mesenchymal pluripotent cell line), the differentiation of cocultured splenocytes into osteoclasts was enhanced along with the inhibition of OPG [37], which result was consistent with our data.…”
Section: Figmentioning
confidence: 99%
“…22 Another study shows that Runx2 contributes to OPG activities. 21 The reason is probably that Runx2 regulates its target genes together with other factors in different osteoblast maturation stages and different cell lineages. Akt1 is an important transcription gene for controlling posttranscriptional levels of osteoblast differentiation 7 ; it interacts with Figure 3.…”
mentioning
confidence: 99%
“…5 The effect of Runx2 function on osteoblast differentiation and OPG expression is controversial. [21][22][23] Some studies show that Runx2 induces RANKL expression and suppresses OPG expression, 24 and osteoblast differentiation was arrested in Runx2 overexpression cells. 22 Another study shows that Runx2 contributes to OPG activities.…”
mentioning
confidence: 99%
“…Orthodontic treatment caused an inflammatory reaction in periodontal tissues under the action of the external force, and orthodontic force was transferred to the periodontal membrane, which induced periodontal tissue remodeling (Thirunavukkarasu et al, 2000;Hendesi et al, 2015). This process required osteoclasts and cementoblasts.…”
Section: Discussionmentioning
confidence: 99%